F D Maurice and the Crisis of Christian Authority. - Morris, Jeremy, 1960- (Christian theology in context., 2008)
F.D. Maurice was a leading nineteenth-century Anglican theologian and social commentator. He pioneered Christian Socialism and became a key influence on the development of the modern Church of England. This study shows his work was driven by a concern to reinvigorate Anglican ecclesiology, and to promote an ecumenism. - ;This book offers a reassessment of the theology of F.D. Maurice (1805-72), one of the most significant theologians of the modern Church of England. It seeks to place Maurice's theology in the context of nineteenth-century conflicts over the social role of the Church, and ove.